Correction: Dilp-2-mediated PI3-kinase activation coordinates reactivation of quiescent neuroblasts with growth of their glial stem cell niche. - Xin Yuan (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pbio.3000721.].